Gamification as a teaching practice - Massário, Marcelo Schaedler (2019)
The present work seeks to present an important reconfiguration of teaching in the current era in relation to technology: the insertion of the practice of Gamification in teaching. This study will be based on a brief contextualization about the insertion of technology in teaching and how it has been constructed throughout history to this day, thus, it aims to understand the practices related to the Gamification method in context of teaching, aiming to answer the problem of "How to Gamify? ", Using a qualitative, descriptive and exploratory research. From this situation, as a result, it was possible to analyze and reveal different recurrent applications of this method, focused on learning. The research also clarifies the increased interest and motivation of young students, who are exposed daily to Gamification in the school environment, bringing a new format of education and engagement.